Environmental monitoring in the area of the Krapivinsky hydroelectric complex during the assessment of the current state and during the construction period of HPP - Prosekov, Alexander; Timoshchuk, Irina; Gorelkina, Alena; Golubeva, Nadezhda; Ivanova, Ludmila; Onopenko, Svetlana (AIP conference proceedings, 2022)
The Krapivinskaya HPP is an unfinished hydroelectric power plant located near the village of Zelenogorsky, Krapivinsky District in the Kemerovo Region, on the Tom River. Its construction started in 1976 and stopped in 1989. One of the reasons for stopping the construction of the hydroelectric complex was the likelihood of the river being polluted by insufficiently untreated industrial effluents discharged near the city of Novokuznetsk. In February 2020, the government of the Kemerovo Region and the Russian energy company PJSC Federal Hydrogenerating Company RusHydro signed cooperation agreement on the project to complete the construction of the Krapivinskaya HPP. According to some experts, on the one hand, the commissioning of the HPP will improve the quality of water in the Tom River for the cities of Kemerovo, Yurga and Tomsk in the conditions of maintaining the existing technogenic load; create a sustainable water supply for the population, industry and agriculture of the Kemerovo and Tomsk regions during off-season periods, especially in dry years; restore the lost navigable value of the river and ensure the possibility of using it as a transport artery for the export and import of coal, timber, etc. On the other hand, when the HPP is put into operation, there are possible risks of a negative impact on the biosphere. In this regard, studies to assess the current state of water quality in the Tom River in the area of the Krapivinsky hydroelectric complex as the main natural factor affecting life in the region and subject to impact as a result of the construction of the HPP, as well as the development of measures to reduce the risks of negative impact at the project implementation stage completion of construction are relevant.